Centering ability of three different mechanized files while instrumenting oval canals - Ajinkya Mansing Pawar (Wolters Kluwer Medknow Publications, 2020)
Purpose: The present study evaluated the centering ability of rotary ProTaper NEXT (PTN; Dentsply Tulsa Dental, Tulsa, OK), reciprocating WaveOne (WO; Dentsply Maillefer, Ballaigues, Switzerland) and vibratory Self-Adjusting File (SAF; ReDent Nova, Ràanana, Israel) when used for instrumenting mandibular premolars with oval canals. Materials and Methods: Ninety oval canals (confirmed using radiovisography, buccolingual dimensions were × 2.5 the mesiodistal canal dimensions) were acquired, preinstrumentation cone-beam computed tomography (CBCT) was taken, and divided into three groups (n = 30) for root canal instrumentation: group 1 - PTN; Group 2 - WO; and Group 3 - SAF. The samples were then subjected to postinstrumentation CBCT. The pre- and postinstrumentation scans were compared at 3 mm, 6 mm, and 9 mm from the apex to obtain the centering ability ratio of the three files. The data collected were analyzed using the one-way analysis of variance test and Duncan's multiple comparison tests. Results: The ratio obtained at 6 mm and 9 mm from the apex did not differ for the mesiodistal dimensions (P > 0.05), but a significant difference was observed when the buccolingual dimensions were considered (P < 0.001). The PTN and WO instrumentation were associated with a very high ratio for buccolingual dimensions. However, SAF instrumentation resulted in well-centered preparation for both the dimensions at 6 mm and 9 mm (P < 0.001). At 3 mm from the apex, the files did not differ in canal preparation (P > 0.05). Conclusion: The SAF instrumentation results in centered preparation when used for instrumenting nonround root canals.